Correction: Light and oxygen induced degradation limits the operational stability of methylammonium lead triiodide perovskite solar cells. Issue 5 (21st April 2016) - Bryant, Daniel; Aristidou, Nicholas; Pont, Sebastian; Sanchez-Molina, Irene; Chotchuangchutchaval, Thana; Wheeler, Scot; Durrant, James R.; Haque, Saif A.
Abstract : Correction for 'Light and oxygen induced degradation limits the operational stability of methylammonium lead triiodide perovskite solar cells' by Daniel Bryant et al., Energy Environ. Sci., 2016, DOI: ; Web:10.1039/c6ee00409a .